2014
DOI: 10.5455/ijmsph.2014.280620141
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in under five children in Turbhe stores urban slums in Navi Mumbai

Abstract: Background: Malnutrition is a problem not only in rural area but also among the urban poor. Also, the urban poor are a neglected segment of population in terms of basic services and amenities. Nutrition in children is affected by various determinants including mother's level of knowledge, attitudes and practices. Hence, this study was conducted in an urban slum setting to understand the extent and determinants of malnutrition in children below five years of age. Aims & Objectives: The study objectives were to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Those who had poorer mental health self-selected themselves as interested in further supports provided by a future intervention. These additional strengths in our participants are similar to the positive attitudes and willingness to learn noted in slum-dwelling mothers in another study [ 27 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Those who had poorer mental health self-selected themselves as interested in further supports provided by a future intervention. These additional strengths in our participants are similar to the positive attitudes and willingness to learn noted in slum-dwelling mothers in another study [ 27 ].…”
Section: Discussionsupporting
confidence: 77%
“…While residents are hard-working, optimistic people, they are plagued by poverty and many other social determinants of health that negatively affect health outcomes. For example, stunting has been noted in 50% of the children in one area of the slum [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Better results were reported in NFHS-4 (J and K), where 46% were breastfed within 1 h of birth. Another study conducted by Mukherjee et al [11] in India reported that 75.5% of the mothers started breastfeeding within 1 h which is similar as reported in our study. Similar observations were found in studies conducted by Shah et al [8], Bentley et al [12], Akorede et al [13], and Ghosh and Shah [14].…”
Section: Discussionsupporting
confidence: 91%
“… 14 But the prevalence seen in this study was higher than in studies conducted in other countries, such as Bangladesh (19.5%), 32 Iran (9.53%) 33 and India (30.3%). 34 The discrepancy may be due to the difference in study settings and subjects. In this study, most of the mothers were uneducated.…”
Section: Discussionmentioning
confidence: 99%